ANALISIS DUPONT SYSTEM UNTUK MENILAI KINERJA KEUANGAN (STUDI KASUS PT. TELKOMUNIKASI INDUSTRI Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2017 - 2021) - Amelia Kusumawardani; Rita Andini (Jurnal Ilmiah Ekonomika & Sains, 2024)
This research aims to determine the value of financial performance at PT Telkomunikasi Industri Tbk using the Du Pont System with the help of TATO (Total Asset Trun Over), NPM (Net Profit Margin), EM (Equity Multiplier), Net Income to determine ROE (Retrun On Equity ), ROA (Return On Assets), ROI (Return On Investment) which are used to find out whether the company is in good condition or not. The analytical method used is Du Pont System analysis which uses telecommunications companies using the company PT Telkomunikasi Industri Tbk to test whether the company is in good condition or not. In this analysis, descriptive qualitative analysis is used which explains how the Du Pont System determines the financial performance of the company PT Telkomunikasi Industri Tbk. The results of this research can be concluded that the existence of the Du Pont System can help investors to find out the financial performance of each company and can compare with other companies whether the company is in good condition or not. In this research, PT Telkomunikasi Industri Tbk is not in a bad condition, it can be seen from the ROI (Return On Investment), ROA (Return On Asset), ROE (Return On Equity) values which have decreased.